2016
DOI: 10.1016/j.agee.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Large grazing birds and agriculture—predicting field use of common cranes and implications for crop damage prevention

Abstract: Increasing numbers of previously threatened large grazing birds (cranes, geese and swans) are causing crop damage along their flyways worldwide. For example, the number of reported incidents of crop damage caused by common cranesGrus grus, followed by regulated inspections and governmental compensation in Sweden, has increased over the last few decades and was valued at ∼200,000 Euros in 2012. Consequently, their impact on agriculture is escalating which raises the need for evidence-informed preventative strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 52 publications
4
36
0
Order By: Relevance
“…Yet, in line with predictions, our findings indicated that cranes were gradually becoming more risk averse, selecting for high quality foraging sites located further away from human disturbance with increasing distance to roost. Our findings correspond with previous studies showing a decreasing probability of crane presence with distance to roost site (Bautista et al 1995, Nilsson et al 2016, presumably because cranes strive to reduce energetic costs of movement (Gils and Tijsen 2007, Elliott et al 2009, Rozen-Rechels et al 2015. The decreasing strength of selection for food availability with distance to the central place is more intricate to explain.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Yet, in line with predictions, our findings indicated that cranes were gradually becoming more risk averse, selecting for high quality foraging sites located further away from human disturbance with increasing distance to roost. Our findings correspond with previous studies showing a decreasing probability of crane presence with distance to roost site (Bautista et al 1995, Nilsson et al 2016, presumably because cranes strive to reduce energetic costs of movement (Gils and Tijsen 2007, Elliott et al 2009, Rozen-Rechels et al 2015. The decreasing strength of selection for food availability with distance to the central place is more intricate to explain.…”
Section: Discussionsupporting
confidence: 90%
“…oat and rye). Similar selection for barley and wheat has been shown in other areas, although selection patterns differ due to local differences in quality and availability of crops (Sugden et al 1988, Nilsson et al 2016. Corn and sunflower stubble fields are often selected over barley and wheat in areas where such crops are cultivated (Lovvorn andKirkpatrick 1982, Alonso et al 1983), which may restrict generalization between staging sites.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations